PENGARUH BAGI HASIL DAN INFLASI TERHADAP DANA PIHAK KETIGA PADA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH - Muhammad Wahyudi; Epita Ernawati Damanik; Anggun Delpita Sari (Jurnal At-Tabayyun, 2023)
This study aims to examine the effect of profit sharing and inflation on third party funds in Islamic commercial banks and Islamic business units. Profit sharing is the main principle in the Islamic banking system, in which the bank's income is obtained through profit sharing with customers. Inflation, on the other hand, is a phenomenon of increasing the general price level in the economy. These two factors are believed to have a significant influence on third party funds, which are one of the main funding sources for Islamic banks. This research method uses a quantitative approach with multiple regression analysis. The data used are secondary data obtained from the financial reports of Islamic commercial banks and Islamic business units during the study period. The results of the analysis show that both profit sharing and inflation significantly affect third party funds in Islamic commercial banks and Islamic business units. Revenue sharing has a strong positive effect, while inflation has a significant negative effect on third party funds.